2018
DOI: 10.1097/prs.0000000000004117
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Color Doppler Ultrasound Imaging for the Assessment of Anterolateral Thigh Flap Perforators: A Prospective Study of 30 Perforators

Abstract: Diagnostic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 11 publications
1
28
0
2
Order By: Relevance
“…17 CCDS has quickly gained momentum and seems to spread faster than other diagnostic modalities for perforator evaluation. 2,10,14,25,[27][28][29] Kehrer et al demonstrated that sensitivity of CCDS was 96.7% with an average distance from the true projection of EP to the CCDS skin marking of 2.45 AE 1.90 mm (range: 0-6 mm). 19 All perforators detected by CCDS and confirmed intraoperatively were sizable (!…”
Section: Discussionmentioning
confidence: 99%
“…17 CCDS has quickly gained momentum and seems to spread faster than other diagnostic modalities for perforator evaluation. 2,10,14,25,[27][28][29] Kehrer et al demonstrated that sensitivity of CCDS was 96.7% with an average distance from the true projection of EP to the CCDS skin marking of 2.45 AE 1.90 mm (range: 0-6 mm). 19 All perforators detected by CCDS and confirmed intraoperatively were sizable (!…”
Section: Discussionmentioning
confidence: 99%
“…Regarding color Doppler, its advantages lie on the wide availability of the exam; on expert hands is quick to perform; it does not involve radiation or the use of contrast and provides hemodynamic information of the vessels, being able to detect the anchoring point to the dermis, thus facilitating the harvesting of thin and ultrathin flaps. 28 On the other hand, its disadvantages are the ability to detect only vessels larger than 0.5 mm, does not provide a three-dimensional (3D) description of the anatomy, to be an operator-dependent test, and it is not easy to perform and to interpret. 29,30 CTA advantages are its ability to capture vessels of smaller caliber than ultrasound, larger than 0.3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, all surgeons need to be proactive about preventing flap ischemia in their surgical planning. Using other medical equipment can help mitigate flap ischaemia-i.e., doppler ultrasound [7], CT angiogram [8,9], and magnetic resonance angiography [10]; by helping to determine the location of vessels supplying the Jenwitheesuk/Mahakkanukrauh/Punjaruk/Jenwitheesuk/Surakunprapha/Punyavong/Winaikosol/Chowchuen/ Limrattanapimpa lesion when it is uncertain whether the vessels were damaged after trauma.…”
Section: Discussionmentioning
confidence: 99%